The Stem Cell Microenvironment and Its Role in Regenerative Medicine and Cancer Pathogenesis. - Pennisi, Cristian Pablo. (River Publishers, 2017)
This book discusses some of the recent advances in stem cell research that may help understanding the properties of the niche that govern stem cell fate. This book emerges as a result of the scientific contributions presented and discussed during the fifth Disputationes Workshop held in Aalborg (Denmark) in April 2014.